Polymyxin B-Associated Nephrotoxicity and Its Predictors: A Retrospective Study in Carbapenem-Resistant Gram-Negative Bacterial Infections - Wu, Xiao-Li; Long, Wen-Ming; Lu, Qiong; Teng, Xin-Qi; Qi, Ting-Ting; Qu, Qiang; He, Ge-Fei; Qu, Jian (Frontiers in Pharmacology, 2022)
Polymyxin B (PMB), as a kind of polymyxins, was widely used in Carbapenem-Resistant Gram-negative Bacteria (CR-GNB) infections. However, adverse reactions such as nephrotoxicity and neurotoxicity limit its use in clinical practice. This study aims to explore the PMB associated with nephrotoxicity and its predictors. Patients who received PMB intravenous drip for more than 72 hours were eligible for the study. Characteristics of patients, concomitant nephrotoxic agents, underlying disease, antimicrobial susceptibility were submitted for descriptive analysis. Univariate analysis and binary logistic regression were used to assess the factors leading to acute kidney injury (AKI). AKI was assessed with serum creatinine variations according to the classification of risk (stage R), injury (stage I), failure (stage F), loss, end-stage of kidney disease. Among the 234 patients with CR-GNB infections who used PMB in our study, 67 (28.63%) of patients developed AKI, including 31 (14.25%) patients in stage R, 15 (6.41%) patients in stage I, and 21 (8.97%) patients stage F. The incident rate of PMB-related nephrotoxicity in patients with normal renal function was 32.82% (43/131). The higher risk factors of AKI include males (odds ratio (OR) =3.237; 95% confidence interval (95%CI) =1.426-7.350), digestive system diseases (OR=2.481 (1.127-5.463)), using furosemide (>20mg/day) (OR=2.473 (1.102-5.551)), baseline serum creatinine (OR=0.994(0.990-0.999)). K Independent sample nonparametric tests showed that baseline serum creatinine and the PMB maintenance dose were associated with the severity of nephrotoxicity (both p<0.05). Male, digestive system diseases, using furosemide (>20mg/day), and high baseline serum creatinine were the independent risk factors of PMB-associated AKI development. The maintenance dose of PMB may be related to the severity of AKI. These risk factors should be taken into consideration when initiating PMB-based therapy. The serum creatinine value should be closely monitored when using PMB.